Survey on magnetic resonant coupling wireless power transfer technology for electric vehicle charging. Issue 12 (13th September 2019) - Mou, Xiaolin; Gladwin, Daniel T.; Zhao, Rui; Sun, Hongjian
Abstract : Wireless power transfer (WPT) technology makes it possible to supply power through an air‐gap, without the need for current‐carrying wires. One important technique of WPT technology is magnetic resonant coupling (MRC) WPT. Based on the advantages of MRC WPT, such as safety and high power transfer efficiency over a long transmit distance, there are many possible applications of MRC WPT. This study provides a comprehensive, state‐of‐the‐art review of the MRC WPT technology and wireless charging for electric vehicle (EV). A comparative overview of MRC WPT system design which includes a detailed description of the prototypes, schematics, compensation circuit topologies (impedance matching), and international charging standards. In addition, this study provides an overview of wireless EV charging including the static wireless EV charging and the dynamic wireless EV charging, which focuses on the coil design, power transfer efficiency, and current research achievement in the literature.